Ice-wedge thermal regime in northern Victoria Land, Antarctica - RAFFI, Rossana; S. SEGA (Institute of Northern Engineering - University of Alaska, 2008)
A study on ice-wedge thermal regime in northern Victoria Land, Antarctica, was conducted by installing data loggers at threee selected sites. Analysis of the thermal regime over two years revealed that in winter that thermal conditions at the study sites are more severe than those identified in the Arctic areas, and they most likely can trigger cracking.